Maternal Risk Factors for Low-Birth-Weight Neonates: A Hospital Based Case-Control Study in Rural Area of Western Maharashtra, India - Deshpande , Jayant D; Phalke , DB; Bangal, V B; Peeyuusha, D; Bhatt , Sushen (National Journal of Community Medicine, 2011)
Low birth weight (LBW) is a major determinant of infant mortality and morbidity. It is generally recognized that the etiology of LBW is multifactorial. Present case control study was conducted with the objective of studying maternal risk factors associated with full term LBW neonates. A total of 200 cases and 200 controls of age 18–35 years who delivered a live-born singleton baby were enrolled. The data information was gathered from the maternal health records and interviewing the mothers of these neonates. All the data were entered into the SPSS package (version 17). Association of the risk factors under study was assessed by applying chi –square test. To assess the strength of association the odds ratio and 95% confidence interval of odds ratio was calculated. Majority of the cases and controls belongs to 20-29 years age group. The proportion of low income, illiterate/primary educated, farm laborer mothers, primiparas, and women with Spacing < 2 years were higher among the LBW newborns. LBW was strongly associated with anaemia [χ2=17.33, p<0.0001]. Significant risk factors identified in univariate analysis included pregnancy-induced hypertension [OR=4.09(1.49-11.19)], pre pregnancy maternal weight <45 kgs [OR=4.41(2.30-8.46)], maternal height <145 cms [OR=2.34(1.17-4.66)] and Inadequate antenatal care (χ2=24.81, p<0.0001). Large number of mothers from rural area were not utilizing or inadequately utilizing antenatal care services. Many risks for LBW can be identified before pregnancy occurs. Health education, socio-economic development, maternal nutrition, and increasing the use of health services during pregnancy, are all important for reducing LBW.